2016
DOI: 10.1248/bpb.b15-00880
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Characterization of HIV-1 Reverse Transcriptase Interactions with Non-nucleoside Reverse Transcriptase Inhibitors

Abstract: Non-nucleoside reverse transcriptase inhibitors (NNRTIs) of human immunodeficiency virus type 1 reverse transcriptase (HIV-1 RT) have been developed for the treatment of acquired immunodeficiency syndrome. HIV-1 RT binding to NNRTIs has been characterized by various biophysical techniques. However, these techniques are often hampered by the low water solubility of the inhibitors, such as the current promising diarylpyrimidine-based inhibitors rilpivirine and etravirine. Hence, a conventional and rapid method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…For NVP binding, the decrease in signal intensity of the upfield free resonance (−61.9 ppm) is concomitant with an increase in the intensity of the downfield NVP‐bound resonance (−59.7 ppm) (Figure A). A similar observation holds for RPV binding, although the shift occurs at lower NNRTI/protein ratios, consistent with the higher affinity of RPV to RT compared to NVP (Figure B). Assuming that dimeric p66 tfmF /p66 tfmF is in equilibrium between NNRTI‐free and bound forms, with two resonances essentially reporting on the binding, NVP and RPV dissociation constants, K D , were estimated to be 32.…”
Section: Resultssupporting
confidence: 78%
“…For NVP binding, the decrease in signal intensity of the upfield free resonance (−61.9 ppm) is concomitant with an increase in the intensity of the downfield NVP‐bound resonance (−59.7 ppm) (Figure A). A similar observation holds for RPV binding, although the shift occurs at lower NNRTI/protein ratios, consistent with the higher affinity of RPV to RT compared to NVP (Figure B). Assuming that dimeric p66 tfmF /p66 tfmF is in equilibrium between NNRTI‐free and bound forms, with two resonances essentially reporting on the binding, NVP and RPV dissociation constants, K D , were estimated to be 32.…”
Section: Resultssupporting
confidence: 78%
“…The 1:1 complex of FKBP:FK506 was observed in 10 mM ammonium acetate at pH 7.5. The authors observed the protein–ligand interactions by electrospray ionization (ESI) MS. Katta and Chait reported the observation of the hemoglobin complex [ 6 ], and we recently reported three cases of protein–ligand interactions: nuclear receptor peroxisome proliferator-activated receptor γ (PPARγ)–endocrine disruptors [ 7 ], protein tyrosine phosphatase PTPRZ–inhibitor [ 8 ], and HIV-1 reverse transcriptase–drugs [ 9 ]. Typically, the MS study of protein–ligand complexes requires the modification of various components and conditions within a mass spectrometer.…”
Section: Early Ms Studies Of Protein–ligand Interactionsmentioning
confidence: 99%
“…They compared the affinities of estrogen, the compounds, an endocrine disrupter, and a phyto-hormone for the estrogen receptor using MS competition experiments and showed that the rank order of the estimated affinities are consistent with their reported K D values. We recently examined the interaction of the human immunodeficiency virus-1 reverse transcriptase (HIV-1 RT) with drugs in different generations by MS under non-denaturing conditions [ 9 ]. The half-concentrations of the drugs where the peak intensities of the HIV-1 RT-drug complexes were equal to those of free HIV-1 RT were well-correlated with the K D values reported in the literature ( Fig.…”
Section: Drug Screening Using Msmentioning
confidence: 99%
See 1 more Smart Citation